Doping-induced microstructural, textural and optical properties of In2Ti1-xVxO5+delta semiconductors and their role in the photocatalytic splitting of water - Shah, Pallavi; Bhange, Deu S.; Deshpande, Aparna; Kulkarni, Mukund S.; Gupta, Narendra M. (Materials Chemistry and Physics, 2009)
The physicochemical properties of V-doped indium titanates (In2Ti1-xVxO5-delta, 0.0 <= x <= 0.2) were investigated by using XPS, powder XRD, UV-vis, SEM and luminescence spectroscopy techniques. The Rietveld refinement of XRD data revealed that even though the V-containing samples were isostructural with In2TiO5 (orthorhombic space group Pnma), a systematic x-dependent variation was noticeable in the Ti-O bond lengths in [TiO6] octahedral units, cell parameters and in the value of delta. XPS results confirmed the coexistence of V5+ and V4+ states, leading thereby to an enhancement in oxygen non-stoichiometry in the doped samples. A loading-dependent progressive shift from 400 to 750 nm was also observed in the onset of the absorption edge, indicating a significant narrowing of the band gap. Furthermore, the samples with higher V-content were comprised of the grain clusters having larger size and an irregular shape. The UV-vis. photoluminescence and thermoluminescence studies indicate that the doping-induced lattice defects may give rise to certain closely spaced acceptor/donor energy levels in between the band gap of host matrix. The indium titanates are found to serve as stable photocatalysts for water splitting under visible light, where oxygen was the major reaction product. The role of microstructural and morphological properties in the photocatalytic activity is discussed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: In2Ti1-xVxO5+delta photocatalysts; Luminescence spectroscopy; Microstructure; Optical properties; Structure-activity relationship; water splitting

Dynamic study of N ` N-dimethylparanitroaniline encapsulated in silicalite-1 matrix using neutron spin-echo spectroscopy - Bhange, Deu S.; Dejoie, C.; Porcher, F.; Malikova, N.; Martinetto, P.; Dooryhee, E.; Anne, M. (European Physical Journal-Special Topics, 2010)
The present work focuses on the dynamic studies of N'N-dimethyl-paranitroaniline (dmpNA) encapsulated in silicalite zeolite. Quasielastic neutron scattering (QENS) experiments are carried out using neutron spin-echo technique. Polarisation of the scattered neutron beam is measured at carefully chosen values of Q = 0.35, 0.9, 1.1 and 1.45 angstrom(-1) at fixed T = 298K and at fixed Q = 0.9 angstrom(-1) at 150, 200, 250 and 298 K. This gives insight into the motion and the related activation energy of the guest dmpNA molecule. The quasielastic signal observed in the present system within the time range considered is due to fast local rotational motions of protons of the end methyl groups. The results are in good agreement with the dynamics of methyl group rotations reported in the literature by back-scattering QENS technique.

Direct synthesis of well-ordered mesoporous Al-SBA-15 and its correlation with the catalytic activity - Bhange, Pallavi; Bhange, Deu S.; Pradhan, Sivaram; Ramaswamy, Veda (Applied Catalysis A-General, 2011)
The synthesis of Al-SBA-15 under milder acidic conditions were made through an adjusting the molar H(2)O/HCl ratio which indicate the formation of Si-O-Al linkages that lead to isomorphous substitution of Si(4+) by some Al(3+) ions. By adjusting the H(2)O/HCl molar ratio, Al gets incorporated into the lattice of SBA-15, which is evidenced by XRD. N(2) adsorption, TEM, (29)Si and (27)Al MAS NMR spectroscopic data. Aluminium incorporated SBA-15 samples retained both structural and textural properties of SBA-15. The (27)Al MAS NMR confirms that a large proportion of the Al is inserted into tetrahedral positions within the framework. The Al(3+) ions could assume a tetrahedral coordination and be part of the hexagonal structure of silica in Al-SBA-15. In the present study, we have examined the effectiveness of Al-SBA-15, as an acid catalyst for the esterification of acetic acid and in benzylation of anisole. The high activity of Al-20 sample in esterification reaction has been attributed to isolated, generally tetrahedrally coordinated, framework Al species. While in benzylation of anisole, the best result was achieved with Al-5 catalyst. The selectivity for benzylanisole increases and that for dibenzylether decreases with increase in the Si/Al ratio of Al-SBA-15. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Al-SBA-15; Benzylation of anisole; Esterification of acetic acid